A High-Pressure System for Studying Oxygen Reduction During Pt Nanoparticle Collisions. Issue 16 (7th December 2020) - Zhang, Yulun; Robinson, Donald A.; McKelvey, Kim; Ren, Hang; White, Henry S.; Edwards, Martin A.
Abstract : Here we report measurements of the oxygen reduction reaction (ORR) at single Pt nanoparticles (NPs) through their collision with a Au microdisk electrode of lower electrocatalytic activity. Performing measurements at an elevated pressure (10-atm, pure O2 ) raises the O2 concentration ∼50-fold over air-saturated measurements, allowing the ORR activity of smaller Pt NPs to be resolved and quantified, compared to measurements taken at atmospheric pressure. Single-NP ORR current vs potential measurements for 2.6, 16, and 24 nm radius citrate-capped Pt NPs, show the catalytic activity of the smallest Pt NPs to be roughly one order of magnitude greater than the activity of the larger NPs. The particle-by-particle nature of our measurement quantifies the distribution of electrocatalytic activities of individual particles, which we determine to be larger than can be explained by the distribution of particle sizes. Additionally, we report that some of the observed ORR current transients contain multiple sharp peaks per single-NP measurement, indicating multiple collisions of a single Pt NP at the electrode surface.